Yield And Quality Of Malt Barley (Hordeum Distichum L.) As Influenced By Seed Rate, Row Spacing And Nitrogen Levels (Applied Biological Research, 2019)
A field experiment was conducted during rabi season 2014-15 at Agronomy Research Farm, CCSHAU, Hisar (India) to assess the effect of seed rate, row  spacing and nitrogen on yield and quality of malt barley. The experiment comprised of two seed rates (87.5 and 100 kg ha-1) and three spacings (22, 20  and 18 cm) in main plots and four nitrogen levels (60, 75, 90 and 105 kg N ha-1)  in sub-plots, laid out in a split plot design. The application of 100 kg seed ha-1 significantly improved grain, protein and malt yield over 87.5 kg seed ha-1. However, the quality parameters like bold grain, hectoliter weight, starch  content, protein content, husk content and malt recovery were at par under  both the seed rates. Row spacing of 18 cm gave significantly higher grain and  malt yield as compared to 22 cm but was at par with 20 cm spacing. The  grain, protein and malt yield increased significantly up to 90 kg N ha-1. It  appears that 100 kg ha-1seed rate, 18 or 20 cm row spacing and 90 kg N ha-1 are optimum for most yield and quality parameters for two rowed barley  under Haryana conditions.
Keywords: Malt recovery; nitrogen; protein; row spacing; seed rate; yield